2021
DOI: 10.3390/rs13214485
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Mining Activities Using Sentinel-1A InSAR Coherence in Open-Pit Coal Mines

Abstract: Long-term continuous monitoring of the mining activities in open-pit coal mines is conducive to planning and management of the mining operations. Additionally, this faciliatates assessment on their environmental impact and supervises illegal mining behaviors. Interferometric Synthetic Aperture Radar (InSAR) technology can be effectively applied in the monitoring of open-pit mines where vegetation is sparse and land cover is dominated by bare rock. The main objective of this study is to monitor the mining activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
7
1
2
Order By: Relevance
“…Sentinel-1 offers global covers and provides SAR data at regular intervals. This has been used in various applications including slope failures and mining-related deformation (Carla et al, 2019;Tang et al, 2020;Wang et al, 2021). The role of open-access Sentinel-1 data enables collaboration between various users (Ramachandran et al, 2021).…”
Section: Open Remote Sensing Datamentioning
confidence: 99%
“…Sentinel-1 offers global covers and provides SAR data at regular intervals. This has been used in various applications including slope failures and mining-related deformation (Carla et al, 2019;Tang et al, 2020;Wang et al, 2021). The role of open-access Sentinel-1 data enables collaboration between various users (Ramachandran et al, 2021).…”
Section: Open Remote Sensing Datamentioning
confidence: 99%
“…Currently, MT-InSAR techniques are developed to monitor large areas such as the whole territory of Germany [46], Norway [47], and Italy [48], or as an alpha version of an infrastructure monitoring and decision-support framework remotIO based on the MT-InSAR introduced by Bakon et al [49]. Many studies showed subsidence results for cities in Europe [2,3,50], the USA [45], and China [51], or of deformation monitoring of earthquakes [4,52], min-ing [22,30,31,53], land and coastal monitoring [2,3,7,23,[39][40][41]54], volcanic activities [55], glacier motions [56], or even illegal mining activities using the decorrelation problem as valuable information [53]. In addition, by combining dual polarization channels VV and VH, the Polarimetric Persistent Scatterer Interferometry technique (PolPSI) can be used to reduce decorrelation effects and achieve better deformation monitoring [57].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the late start of the monitoring technology, immature monitoring methods and low-accuracy monitoring results are frequent [ 39 , 40 ]. However, this phenomenon gradually decreases with the improvement of the research methods.…”
Section: Introductionmentioning
confidence: 99%